REFORMASI HUKUM (DAGANG) KAJIAN KHUSUS TERHADAP PERLUNYA UU ANTI MONOPOLI ATAU PERSAINGAN USAHA TIDAK SEHAT PASCA UU CIPTA KERJA - Jumhana, Enjum; Priatna, Achmad Nashrudin (LPPM Universitas Bina Bangsa, 2023)
The business world is inseparable from fair and reasonable competition in business activities, so that there is no central economic power for certain business sectors, while remaining obedient to existing laws and regulations. Law Science does not see chaos, but rather as a component of a system where there is a bond of legal principles. As a legal system, it contains orders, rules which constitute a unified whole of parts or elements that are interrelated to one another. In principle, the business area, in order to obtain maximum revenue, is normal behavior, as long as there are no monopolistic practices, but in reality it is always colored by the power of unfair competition groups. Therefore it is not easy to interpret the meaning and causes of monopolistic practices which are the implementation of Law No.5 Tahun 1999 which are directly related to business activities as well as the economy of a nation